Bioerosion structures in a Late Cretaceous mosasaur from Antarctica - Talevi, Marianella; Brezina, Soledad Silvana (Facies)
Bioerosive structures in the cortical region of a vertebra from a mosasaur fall in the López de Bertodano Formation (Upper Maastrichtian) in Seymour Island (Isla Marambio), Antarctica, are reported. The traces studied are similar but not coincident with the described microborings in other fossil bone remains. The morphology and extension of these bioerosive structures are considered as the result of the activity of endolithic organisms on the original vascular channels of the bone. They are approximately straight, anastomosed, and commonly filled with an opaque mineral and framboidal pyrite. As most of the bone structure is well preserved, only the small portion of the cortical region was exposed to the microorganisms’ activity. This would mean that the mosasaur individual died well earlier than the burial event. This is their first report of this type of bioerosive structures in a mosasaur fall. Fil: Talevi, Marianella. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina Fil: Brezina, Soledad Silvana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina